A Study on the Need of Girls Education in India: The Role of Girls' Education in Gender Equality and Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2016)
One of the pernicious features of gender inequality is that it feeds on itself parents may have lower aspirations for their daughters than for their sons, and so their daughters too have lower aspirations for themselves. Yet, if given the chance, girls and women can have the confidence and skills to be change-makers. A recent review of the literature on women’s leadership found that most women leaders started early, engaging in education and leadership activities as adolescents. A number of cases—from India to Rwanda—have shown that having women leading in their communities can make a difference, driving policies and programs that improve family and community well-being.Empirical research finds that more gender equality in education is correlated with higher economic growth. In addition, research concludes that years of schooling is not an adequate measure of educational progress. Instead, it is the quality of schooling that matters.